Intranasal inoculation of female BALB/c mice with replication-deficient human adenovirus type 5 expressing SARS-CoV‐2 nucleocapsid protein aggravates lung pathology upon re-encountering the antigen - Junxia Cao; Hongjing Gu; Xueting Zhang; Hongfang Yun; Jiarong Li; Chuan-Yimu Si; Jiyan Zhang; Hui Wang (Virus Research, 2023)
Preclinical studies indicate that SARS-CoV-2 nucleocapsid (N)-based vaccines, along with other viral protein(s), confer protection in various animal models against infection by SARS-CoV-2 ancestral virus and variants of concern. However, the optimal vaccination procedure and the role of N-specific host adaptive immune responses remain elusive. Here, we report that intranasal inoculation with replication-deficient human adenovirus type 5 expressing SARS-CoV‐2 N protein (Ad5-N) conferred no protection in the lung of female BALB/c mice upon re-encountering the antigen, either by 10-fold Ad5-N re-exposure or sublethal infection of mouse-adapted SARS-CoV-2. By contrast, this procedure led to aggravated lung pathology with more necroptotic CD3+ T cells and Ly6G+ granulocytes, which was associated with the accumulation of IFN‐γ‐expressing antigen-experienced CD4+ and CD8+ T cells. These findings pre-caution the clinical application of this vaccination procedure. Furthermore, our data suggest that excessive host adaptive immune responses against N protein contributes to COVID-19 pathogenesis.